Transfer of Cosmetic Emulsion Cream Technology from Laboratory to Pilot Phase - M. A. Burakova; O. N. Abrosimova; Yu. M. Ladutko; I. E. Smekhova (Разработка и регистрация лекарственных средств)
Introduction. When transferring the technology of cosmetic emulsion cream from laboratory conditions to semi-industrial equipment, it is necessary to determine the critical process parameters that will allow achieving results without losing the quality of the final product.Aim. The aim of the study is to confirm the effectiveness of the developed technology for the production of emulsion cream under scaling conditions.Materials and methods. As active substances were used badan thick-leaved extract dry, salicylic acid, dimethicone, menthol and octypyrox; emollients – grape seed oil, coconut oil, castor oil; emulsifiers and co-emulsifiers – distilled monoglycerides, emulsion wax, anhydrous lanolin, Cremophor A25; humidifier – glycerin; alkaline agent, pH regulator – triethanolamine; preservative – Euxil 9010; fragrance – essential oil of rosewood, solvent – purified water. Phase mixing and emulsification were carried out in a PRS AR 403 planetary mixer (ERWEKA GmbH, Germany), dosing into a sealed plastic container was carried on an FDS II AR 403 ointment dosing unit (ERWEKA GmbH, Germany). The study of the physicochemical and structural-mechanical properties of the cream was carried out in accordance with GOST 29188.2-2014 and GOST 29188.3-91.Results and discussion. Under scaling conditions, 3 pilot series of cosmetic emulsion cream for the prevention of dry seborrhea of the scalp based of badan thick-leaved extract dry have been developed. The cream obtained both in the pilot and laboratory phases met all the requirements of the Technical Regulations of the Customs Union (TR CU) 009/2011 "On the safety of perfumery and cosmetic products", which confirms the reproducibility of the developed production technology. A 20-fold increase in loading did not affect the methods of introducing the components and their percentage. To determine the possibility of technology transfer from laboratory conditions to semi-industrial production conditions, the technological characteristics of the equipment were analyzed for the ability to carry out the required technological process, using the Ishikawa diagram, risks were identified and causal relationships of the production. The most important indicators of the technological process have been established – these are the temperature, the number of revolutions of the mixer and the mixing time.Conclusion. On the semi-industrial equipment of the GMP training center, the technology of obtaining a cosmetic emulsion cream based on badan thick-leaved extract dry. A causal diagram (Ishikawa diagram) was compiled. Taking into account possible risks in the production of emulsion cream (number of revolutions of the mixer, stirring time, temperature) made it possible to obtain a stable product that meets all the requirements of TR CU 009/2011 "On the safety of perfumery and cosmetic products". The reproducibility of the technological process is shown.